2015
DOI: 10.4313/teem.2015.16.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Real Time ECG Monitoring Through a Wearable Smart T-shirt

Abstract: A wearable sensing ECG T-shirt for ubiquitous vital signs sensing is proposed. The sensor system consists of a signal processing board and capacitive sensing electrodes which together enable measurement of an electrocardiogram (ECG) on the human chest with minimal discomfort. The capacitive sensing method was employed to prevent direct ECG measurement on the skin and also to provide maximum convenience to the user. Also, low power integrated circuits (ICs) and passive electrodes were employed in this research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…So the HBC-based ECG with non-contact capacitive coupling electrodes can provide a sufficient reliability in both the time and frequency domains. Moreover, compared to the performances shown in [6,7], our HBC-based ECG provides a clearer QRS-wave and a clearer heart rate variability analysis result, which suggests a possibility for diagnostic purpose. As for the difference in Fig.…”
Section: Performance Comparison With Commercial Ecgmentioning
confidence: 79%
See 1 more Smart Citation
“…So the HBC-based ECG with non-contact capacitive coupling electrodes can provide a sufficient reliability in both the time and frequency domains. Moreover, compared to the performances shown in [6,7], our HBC-based ECG provides a clearer QRS-wave and a clearer heart rate variability analysis result, which suggests a possibility for diagnostic purpose. As for the difference in Fig.…”
Section: Performance Comparison With Commercial Ecgmentioning
confidence: 79%
“…A prototype system was introduced in [5] to measure impedance over capacitive electrodes, which contributed to draw a conclusion about the applicability of such capacitive electrodes for ECG detection. For realising the non‐contact capacitive coupling detection, placing small flexible electrodes into cotton pockets of a worn tight NIKE Pro combat T‐shirt was proposed in [6], and inserting a thin cloth between the sensing electrodes and the skin of a subject's dorsal surface was proposed in [7]. Both the two studies focus on the use of capacitive electrodes, and the detected ECG signals were confirmed useful for non‐diagnostic purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Table 4 presents all the different sensors identified across all prototype design studies. [32,57,60,[67][68][69]78,80,88,105,118] 8 (16) Respiratory only [31,42,47,51,79,87,104] 2 (4) Electromyography only [38,103] 27 (54) Numerous signals [3,22,[24][25][26]33,34,36,37,39,40,44,50,58,59,77,80,86,99,102,113,114,120]…”
Section: Prototype Design Studiesmentioning
confidence: 99%
“…Nowadays, such devices are pervasive in several aspects of our lifestyle, enabling extensive and real-time monitoring of the wearer's psycho-physical state. Thus, several devices, including wireless communication modules, sensors, and computational units, have been developed and included inside a t-shirt [1] or connected to a belt [2] or integrated inside shoes [3]. Thanks to the recent scientific and technological advances in the biotechnology and bioengineering fields, considering the high computational capability of new processors with high level of integration and taking into account the availability of accurate, reliable and less invasive integrated sensors, the most recently manufactured wearable devices are smart, small and maintenance-free [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Figure13. Histogram with reported the power conversion efficiency of employed flexible solar cells, as function of the irradiance level 1 , when exposed to the sunlight (blue bars) and Ne lamp (red bars) 1. Irradiance values calculated from the illuminance ones [lux] in Table2, using distinct conversion coefficients [Wm −2 lux −1 ] for sunlight and Ne source (respectively 0.0079 and 0.0111), known the area of two Size 2 cells.…”
mentioning
confidence: 99%